Villages in Forest Areas in Java: Agrarian Reform Policy-Social Forestry in Banyuwangi - Syanurisma, Syarli (Marcapada: Jurnal Kebijakan Pertanahan, 2022)
The overlapping claims on forest areas is due to the presence of interested parties in its management from private companies, local communities, local governments, and the State Forestry Public Company (Perusahaan Umum Kehutanan Negara/Perhutani). This triggered tenurial conflicts in forest areas. Recognition of community rights in forest areas can be realized if proposed through the right path and process, by preparing data owned by the community. Therefore, it is necessary to identify the authorization, ownership, utilization, and use of community land in forest areas with the aim to understand the land tenure in forest areas. This article aims to examine the typology of land tenure conflicts in forest areas and identify the authorization, ownership, use, and utilization of community land in forest areas. The method of this study is qualitative with descriptive and historical analysis. Meanwhile, the data collection includes observations, interviews, and document studies. The results of this study indicated that there were 309 land plots claimed by the community in forest areas. The land plots have long been controlled, then became a settlement and agricultural land since 1941. As a result, forest areas that have become settlements are eligible to be released and then followed up with an agrarian reform policy. Meanwhile, for arable land, a social forestry scheme can be proposed.